Faktor-Faktor Yang Berhubungan dengan Kejadian Dysmenorrhea Primer Pada Remaja Putri - Marleni leni (STIKES Citra Delima Bangka Belitung, 2021)
Dysmenorrhea is a menstrual disease that causes physical discomfort and can interfere with daily activities. Dysmenorrhea often attacks adolescent girls in their productive age. The incidence of dysmenorrhea in the world is more than 50% of women experiencing dysmenorrhea, while in Indonesia it reaches 55% of adolescents experiencing dysmenorrhea. The results of the preliminary study showed that from 20 female students there were 11 (55%) who experienced dysmenorrhea and 9 people (45%) did not experience dysmenorrhea. The purpose of this study was to determine the factors associated with dysmenorrhea. Methods: This research is a descriptive analytic study with a cross sectional design. The population of this study was all 106 young women of class X SMA Negeri 1 Banguntapan Bantul. The sampling technique used was proportionate stratified random sampling with a sample size of 84 people. Data analysis using Chi-square test. Results: Teenage girls who experienced primary dysmenorrhea at SMA Negeri 1 Banguntapan Bantul were 77.4%. There was a relationship between a family history of dysmenorrhea and the incidence of dysmenorrhea (p value = 0.000). There is no relationship between menarche at an early age, amount of menstrual blood, duration of menstruation, and nutritional status with the incidence of dysmenorrhea. Conclusion: The factor that influences the incidence of dysmenorrhea in class X adolescent girls at SMA Negeri 1 Banguntapan Bantul is a family history of menstrual pain.